2023
DOI: 10.1021/acsapm.3c01732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gallic Acid-Derived Plasticizers for Polyvinyl Chloride Featuring Excellent Plasticization, Thermo-Stability, and Migration Resistance

Jihuai Tan,
Nengkun Huang,
Jing Wu
et al.

Abstract: The development of a facile and environmental strategy for manufacturing a natural aromatic-derived plasticizer for poly(vinyl chloride) (PVC) featuring excellent plasticization, UVshielding, and thermostability, together with migration resistance, is still a challenge. Herein, a series of gallic acid-derived polypropylene glycol monomethyl ether esters with natural aromatic rings (TGPME-n, n = 1, 2, or 3 referring to the number of methylethoxy units in the structure of TGPME-n) were developed as plasticizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…From the photos, the transparency of PLA/HDA-2 n is obviously better than that of PLA/DOTP, which indicates that the compatibility of HDA-2 n with a PLA carrier is better than that of the traditional plasticizer, DOTP. With an increase in the number of ethoxy units, the transparency of plasticized PLA samples increased continuously, which was also consistent with a previous report [ 34 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…From the photos, the transparency of PLA/HDA-2 n is obviously better than that of PLA/DOTP, which indicates that the compatibility of HDA-2 n with a PLA carrier is better than that of the traditional plasticizer, DOTP. With an increase in the number of ethoxy units, the transparency of plasticized PLA samples increased continuously, which was also consistent with a previous report [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…Migration resistance tests adhered to the GB/T3830-2008 standard [ 34 ], submerging the sample (20 × 20 × 1 mm) in an n-hexane solution at 23 ± 2 °C and 50 ± 10% humidity. Samples were dried at 50 °C for 6 h, and the mass loss rate was determined via Equation (1): where W before and W after represent the weight of the PLA samples before and after the test, respectively, and x represents the initial concentration of plasticizer in the PLA sample, testing five samples per set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This slight elevation could be attributed to the potential incompatibility of ECASO at higher loadings in the PVC sheet. 7,25,26 The study demonstrated that the addition of ECASO as a plasticizer in PVC systems effectively reduced the T g , indicating enhanced plasticization. An optimal DOP: ECASO ratio of around 40:60 appeared to maximize the plasticizing effect.…”
Section: Dsc Analysismentioning
confidence: 90%